1979
DOI: 10.1002/1097-0142(197903)43:3<810::aid-cncr2820430306>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis in differentiated thyroid cancer

Abstract: Six hundred patients with primary differentiated thyroid carcinoma had follow-up studies for a minimum of 15 years and a maximum of 45 years. Recurrence rate and death rate were significantly different in defined high-risk and low-risk groups of patients. These basic risk groups were defined by age and sex alone; low risk consisted of men 40 years of age and younger and women 50 years of age and younger whereas the high-risk group were older patients. Recurrence and death rates in patients at high risk were 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
6
11

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(140 citation statements)
references
References 12 publications
5
116
6
11
Order By: Relevance
“…Results from the Cox proportional hazards regression models identified and verified a series of risk predictors for mortality in DTC, including sex, age, and advanced stage, which were consistent with previous studies 19, 20. Then, we conducted subgroup analysis for the effects of marital status on survival in patients stratified by them.…”
Section: Resultssupporting
confidence: 83%
“…Results from the Cox proportional hazards regression models identified and verified a series of risk predictors for mortality in DTC, including sex, age, and advanced stage, which were consistent with previous studies 19, 20. Then, we conducted subgroup analysis for the effects of marital status on survival in patients stratified by them.…”
Section: Resultssupporting
confidence: 83%
“…The first report from the Lahey Clinic Foundation (Cady et al 1979) used three prognostic factors for the analysis of risk in cases of DTC, namely age (cut-off 40 years for men and 50 years for women), gender and histological type: follicular vs papillary. Applying the same prognostic factors as stated in the first publication of the AMES Table 2 Characteristics of the population in terms of the recurrence (REC) of differentiated thyroid carcinoma and overall survival (OS).…”
Section: The Ames Classificationcontrasting
confidence: 58%
“…Age at the time of diagnosis, gender, histological type, tumour size and extrathyroidal invasion have been found previously to be associated with a poor clinical outcome (Cady & Rossi 1988, De Groot et al 1990, Hay 1990, Schlumberger & Pacini 1999, while the prognostic impact of regional lymph node metasases is still a controversial issue (Cady & Rossi 1988, De Groot et al 1990, Frankenthaler et al 1990, Akslen et al 1991, Sellers et al 1992. The presence of distant metastases at the time of diagnosis is a recognised factor for a poor prognosis (Cady et al 1979, Hay 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that the age of the patient is an important prognostic factor in papillary and follicular carcinomas (Crile and Hazard, 1953;Cady et al, 1979), whereas others (Franssila, 1975;Byar et al, 1979;Hay et al, 1993) have great emphasis on age, sex and tumour status in the scoring system. Shi and Farid (1993) reported a negative correlation between expression of TSH-R mRNA and tumour stage in most patients.…”
Section: Resultsmentioning
confidence: 99%